First language use among second language teachers: Views vs practice - Romli, Noor Hayati binti; Abd Aziz, Mohd Sallehhudin bin; N.Krish, Pramela Krish (Jurnal Cakrawala Pendidikan, 2022)
Although the Grammar Translation Method (GTM) had been shunned in second language teaching, the stigma of using the first language (L1) in teaching the second language (L2) has been continuously debated by scholars and teachers. Commonly, L2 teachers support the monolingual approach as they are exposed to this approach in their teaching training courses. However, previous studies revealed that teachers’ stance towards L2 teachers is contrary to how they utilise L1 practice in the teaching process. This research study aims to explore the use of L1 (Bahasa Melayu) by L2 (English) teachers during the teaching process and to examine whether their beliefs matched their L1 practice. A total of eight English teachers from several schools in Pahang, Malaysia were interviewed and their lessons were recorded. The data from the interviews and lessons were thematically analysed using NVivo 12 software. The results demonstrated that the teachers had utilised Bahasa Melayu (BM) for certain functions and that their beliefs towards L1 actually corresponded to their language use in the L2 classrooms. This study suggests that it is imperative to look further into this matter and assist teachers in systematically using L1 in the L2 classrooms.